التدوير الوظيفي وأثره على الفساد الإداري لدى موظفي القطاع الحكومي في الجمهورية العربية السورية دراسة ميدانية على العاملين في القطاع الحكومي في مدينة دمشق (Latakia University Journal - Economic and Legal Sciences Series, 2018)
سعت الدراسة الحالية إلى التعرف على مدى تأثير التدوير الوظيفي على الفساد الإداري لدى موظفي القطاع الحكومي في الجمهورية العربية السورية، كما هدفت الدراسة إلى إلقاء الضوء على واقع تطبيق التدوير الوظيفي في مؤسسات القطاع الحكومي، وتحديد العلاقة بين تطبيق التدوير الوظيفي والحد من تفشي ظاهرة الفساد الإداري داخل المؤسسات المدروسة، ولتحقيق أهداف الدراسة تم سحب عينة عشوائية من رؤساء وأعضاء مجلس الإدارة ومديرين ورؤساء أقسام في مؤسسات وشركات القطاع الحكومي في مدينة دمشق، وتكونت هذه العينة من (96) مفردة وتم جمع بيانات الدراسة من خلال استخدام استبانة مخصصة لهذا البحث مؤلفة من (18) بند تتعلق بالتدوير الوظيفي وأثره على الفساد الإداري. وتوصلت الدراسة إلى العديد من النتائج أهمها: يعتبر التدوير الوظيفي أحد أهم استراتيجيات تطوير أداء العاملين والمؤسسات على حدٍ سواء كونه يساهم بإكساب الموظفين خبرات جديدة ومهارات متنوعة وتطوير العمل والالمام بالمهام المختلفة للمؤسسة ويحد من سوء استغلال السلطة، ويخلق المنافسة بين العاملين كما يساهم التدوير الوظيفي في الحد من معدلات ترك العمل ويخفف من سلبيات الروتين والبيروقراطية في العمل، كما يساهم التدوير الوظيفي في الحد من الفساد الإداري داخل مؤسسات القطاع الحكومي. The current study aimed to recognize the extent of the effect of job rotation on administrative corruption among public sector employees in the Syrian Arab Republic. The study also aimed to highlight on the reality of applying job rotation in public sector institutions, identifying the relationship between applying job rotation and reducing the outbreak of administrative corruption phenomenon within studied institutions. To achieve the objectives of the study, random sample has been chosen from the heads and members of the Board of Directors and directors and heads of departments in the institutions and companies of the public sector in the city of Damascus, this sample has been consisted of (96) elements and the data of the study have been  collected by the use of a questionnaire dedicated to This research consists of (18) items related to job rotation and its effect on administrative corruption. The study reached several results, the most important are: Job rotation considers one of the most important strategies of developing the performance of employees and institutions alike, as it contributes to providing employees with new experiences and diverse skills, developing job and knowledge of the different tasks of the institution, and reducing abuse of power, creating competition among employees. Also the job rotation contribute in reducing the rate of leaving job and the disadvantages of routine and bureaucracy at job, moreover, and the job rotation contributes to reducing administrative corruption within public sector institutions.